A failure mechanics and strength optimization study for patched laminates. (15th October 2019) - Kussmaul, Ralph; Zogg, Markus; Ermanni, Paolo
Abstract: Fiber patch placement (FPP) is a manufacturing technique for variable-stiffness composites structures. Using FPP, a component is assembled from a multitude of discrete fiber patches. Thus, FPP allows tailoring a composite layup to local load states. However, complex stress distributions occur due to discontinuous fibers at patch edges. This paper investigates the failure of unidirectional patched laminates and assesses the influence of governing design parameters on their strength by nonlinear FE analyses. It is found that, depending on their configuration, fiber breakage, yield-slip, or interface fracture are the leading causes of failure. Moreover, the study reveals that the outer layers of patched laminates are much more susceptible to failure than the inner layers. Based on these findings, three distinct patch overlapping patterns are derived, with each of them having their benefits at different locations in the design space. Lastly, strength optimization measures are investigated, aiming at a load reduction of the outer layers. Patched laminate configurations are found which, for intermediate patch length and thickness, feature up to 70% tensile strength retention compared to continuous laminates from the same material. The findings of this work give valuable guidance for the design and analysis of patched laminates.